Root and tuber crops in Montserrat - Fletcher, R.E. (International Center for Tropical Agriculture, 1986)
The situation of root and tuber crops in Montserrat is presented. The main cropping systems, available land, socioeconomic factors, production levels, productivity, imports, and price structure and markets are discussed. Cassava is almost unknown in Montserrat; it is specifically grown for processing into cassava bread during the festival season. The crop is rarely grown in pure stand, but is planted along field borders and contours, and intercropped with pigeon pea, sweet potato, and aroids. The recommendations given include that of conducting more studies on cassava to improve its production and introduce small-scale processing. (CIAT)